'Kasi curriculum': what young men learn and teach about sex in a South African township. Issue 4 (4th July 2019) - Hodes, Rebecca; Gittings, Lesley
ABSTRACT: Sex education within the formal bounds of school curricula or clinic consultation is traditionally conceived as age-appropriate and accurate information, delivered by a sanctioned adult such as a nurse or teacher. This article explores another kind of curriculum – taught and learned among young men themselves in the kasi (township) in which they live. Findings are based on primary data gathered during interviews and research workshops with boys and young men (aged 14–22), including focus group discussions and participatory research exercises. In exploring young men's sexual ideas, practices, hopes and fears, it focuses on three themes: (i) consent and coercion; (ii) pleasure and risk; and (iii) advice and authority. We examine diverse perspectives on these themes, and trace the tensions and ambiguities that surface within young men's accounts. We focus in particular on contradictions between what is learned about sex through formal curricula, and what is learned through peers and older men, including within ulwaluko (a rite of passage of traditional initiation and circumcision for Xhosa men).